Engineering students' perception of academic dishonesty at an American university in the UAE - Tabsh, Sami W.; El-Kadi, Hany A.; Abdelfatah, Akmal S. (IEEE Global Engineering Education Conference, 2016)
In order to gain insight into students' views on the subject, engineering students at an American university in the Middle East were recently asked through a survey about their perception of various academic dishonesty issues. A questionnaire was developed and distributed to 588 engineering students in 2012. It was administered in several engineering classes of different levels in all the departments of the college. The survey also sought information on class level, gender, and major. It gathered students' opinion on 11 questions related to various matters on academic dishonesty, including awareness of student academic integrity code, perception of occurrence of various academic integrity violations, reasons for committing such acts, professors' role in enforcing penalties against violators, and recommendations to curb violations of academic integrity in the future. In general, the results of the study showed that the majority of the students are aware of the academic code of ethics and copyright laws. The main reasons for violating the code of ethics included the difficulty of courses, intensity of assignments, pressure for attaining high grades, laziness, and lack of adequate instructions by some professors. Students thought that cheating on exams does not occur as frequently as cheating on out-of-class assignments. They believed that a large number of faculty address academic dishonesty in their courses and are willing to impose penalties on those who commit acts of dishonesty. Students suggested that the best ways by faculty to reduce violations of academic integrity on campus include catching violators, giving more time to complete the assigned work, providing reasonable amount of work, and reducing the difficulty of exams. It is believed that such results are useful in enhancing strategies that are currently in place for curbing behavior related academic dishonesty.